A BITAGAP e o estudo da historiografia medieval portuguesa (a propósito da nova versão desta base de dados) - Filipe Alves Moreira (Medievalista)
This article reflects on the importance of BITAGAP for the study of Portuguese medieval historiography. It also includes some considerations on recent works in this field.